Anatomically corrected malposition of the great arteries: Review of the literature. (December 2016) - Ait Ali, Lamia; Sicari, Rosa; Festa, Pierluigi
Abstract: Anatomically corrected malposition of the great arteries (ACMGA) is a rare form of congenital heart disease in which the great arteries arise above the anatomically correct ventricles but are abnormally related to the ventricles and one to the other with aorta in an anterior position. The diagnosis is specially challenging in adult patients with poor acoustic window. A review of published cases on PubMed, was performed in order to provide insights and potential pitfalls in diagnosing this clinical condition mainly in biventricular ACMGA. Highlights: ACMGA is a very rare form of congenital heart disease. ACMGA is often misdiagnosed as L-TGA. CMR is a valid tool for the diagnosis of ACMGA.